Disease‐specific health‐related quality of life (HRQL) instruments for food allergy: protocol for a systematic review - Salvilla, Sarah A; Panesar, Sukhmeet S; Patel, Shyamal; Rader, Tamara; Muraro, Antonella; Roberts, Graham; de‐Blok, Bertine Flokstra; Dubois, Anthony; Sheikh, Aziz (Clinical and translational allergy, 2013)
Background The European Academy of Allergy and Clinical Immunology is in the process of developing its Guideline for Food Allergy and Anaphylaxis, and this systematic review is one of seven inter‐linked evidence syntheses that are being undertaken in order to provide a state‐of‐the‐art synopsis of the current evidence base in relation to epidemiology, prevention, diagnosis and clinical management, and impact on quality of life, which will be used to inform clinical recommendations. The aim of this systematic review will be to determine which validated instruments can be employed to enable assessment of the impact of, and investigations and interventions for, food allergy on health‐related quality of life. Methods Seven bibliographic databases were searched from their inception to September 30, 2012 for disease‐specific HRQL questionnaires that were specifically designed for use with patients/carers and any articles relating to the description, development and/or the validation of the above identified HRQLs. There were no language or geographic restrictions. We will assess the development of the instruments identified and their performance properties including: validity; generalizability; responsiveness; managing missing data; how variation in patient demography was managed; and cross‐cultural and linguistic adaptation, using a previously reported quality assessment tool. Discussion Using appropriately developed and validated instruments is critical to the accurate evaluation of HRQL in people with food allergy. This review will systematically appraise the evidence on the subject and help to identify any gaps.